Metabolism of reverse triiodothyronine by isolated rat hepatocytes. - Rooda, S J (1987)
Reverse triiodothyronine (rT3) is metabolized predominantly by outer ring deiodination to 3,3'-diiodothyronine (3,3'-T2) in the liver. Metabolism of rT3 and 3,3'-T2 by isolated rat hepatocytes was analyzed by Sephadex LH-20 chromatography, high performance liquid chromatography, and radioimmunoassay, with closely agreeing results. Deiodinase activity was inhibited with propylthiouracil (PTU) and sulfotransferase activity by sulfate depletion or addition of salicylamide or dichloronitrophenol. Normally, little 3,3'-T2 production from rT3 was observed, and 125I- was the main product of both 3,[3'-125I]T2 and [3',5'-125I]rT3. PTU inhibited rT3 metabolism but did not affect 3,3'-T2 clearance as explained by accumulation of 3,3'-T2 sulfate. Inhibition of sulfation did not affect rT3 clearance but 3,3'-T2 metabolism was greatly diminished. The decrease in I- formation from rT3 was compensated by an increased recovery of 3,3'-T2 up to 70% of rT3 metabolized. In conclusion, significant production of 3,3'-T2 from rT3 by rat hepatocytes is only observed if further sulfation is inhibited.